2005
DOI: 10.1111/j.1471-0528.2005.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of vaginal prolapse severity tosymptoms and quality of life

Abstract: Objective To assess the relationship and location of vaginal prolapse severity to symptoms and quality of life.Design A prospective observational study.Setting Urogynaecology Unit, Imperial College, St Mary's Hospital, London.Population Women with and without symptoms of vaginal prolapse.Methods All women completed a validated Prolapse Quality of Life (P-QOL) questionnaire. This included a urinary, bowel and sexual symptom questionnaire. All women were examined using the Pelvic Organ Prolapse Quantification sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
156
3
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(179 citation statements)
references
References 23 publications
5
156
3
15
Order By: Relevance
“…This is a validated disease-specific questionnaire used to assess both symptoms and QoL in women with pelvic organ prolapse and is used to determine the impact of urogenital prolapse on daily life. 1 The pQoL marks each domain score from 0 to 100. We arbitrarily classified 'bother' as minimal, mild, moderate and marked if scores ranged from 0 to 25, 25-50, 50-75 and 75-100, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a validated disease-specific questionnaire used to assess both symptoms and QoL in women with pelvic organ prolapse and is used to determine the impact of urogenital prolapse on daily life. 1 The pQoL marks each domain score from 0 to 100. We arbitrarily classified 'bother' as minimal, mild, moderate and marked if scores ranged from 0 to 25, 25-50, 50-75 and 75-100, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1 Increased life expectancy and an expanding elderly population means that urogenital prolapse remains an important condition particularly since the majority of women may now spend one-third of their lives in the postmenopausal state. 2 In a retrospective cohort study of 149 554 women, the lifetime risk of having surgery for urogenital prolapse was 11%, and 29.2% of women required repeat surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The issue that determination of the degree of prolapse before and after the treatment alone is insufficient for the assessment of the outcome has been raised by many authors [12][13][14]. Decisions about the management should also be based on the quality of life of the treated women.…”
Section: Discussionmentioning
confidence: 99%
“…10 Allesandero noted stronger relationship between posterior wall prolapse and bowel complains than anterior prolapsed and urinary complains. 11 Weber A found that women with prolapse have bowel symptoms but these are not correlated with severity of posterior vaginal wall prolapse. 12 Present study reveals that women with prolapse have bowel symptoms, but they are not correlated with severity of posterior vaginal wall descent.…”
Section: Discussionmentioning
confidence: 99%